Perming & relaxing complete course - 1936-; Ediciones Prensa y Video (Barcelona : Ediciones Prensa y Video, 1996)
Features hairstyles by Luis Llongueras Batlle
Videodisc 1. Basic systems and processes to curl and perm straight or wavy hair (61 min.) -- Videodisc 2. Basic systems and processes to straighten and relax curly hair (58 min.) -- Videodisc 3. Llongueras method fashion perming processes and special techniques (57 min.) -- Videodisc 4. Llongueras method fashion perming processes and special techniques (58 min.)
DVD
In Spanish, using translator for English.
Keywords: Haircutting; Permanent waving; Hairstyles; Hair -- Dyeing and bleaching